Archaeology on medieval knights' manor houses in Poland - Marciniak-Kajzer, Anna (2016)
The relicts of medieval knight’s manor in Poland today are so called ‘grodziska stozkowate’ (motte) - the anonymous hills having in themselves remnants of wooden buildings, exceptionally made of stone or brick and numerous tiny artifacts being the trace of the past household equipment. Unlike to the castles they are not so often visited but more often destroyed. The book presents the image of medieval knight’s manor, which we know due to archaeological excavations carried on for half a century. Description of buildings household equipment and movables used by the people of the past was completed by transfers from written sources which allows for better understanding the live of mediaeval knights’ family. Stanisław Kołodziejski...